Ethnic Differences in Body Fat Deposition and Liver Fat Content in Two UK‐Based Cohorts. Issue 11 (16th September 2020) - Alenaini, Wareed; Parkinson, James R. C.; McCarthy, John P.; Goldstone, Anthony P.; Wilman, Henry R.; Banerjee, Rajarshi; Yaghootkar, Hanieh; Bell, Jimmy D.; Thomas, E. Louise
Abstract : Objective: Differences in the content and distribution of body fat and ectopic lipids may be responsible for ethnic variations in metabolic disease susceptibility. The aim of this study was to examine the ethnic distribution of body fat in two separate UK‐based populations. Methods: Anthropometry and body composition were assessed in two separate UK cohorts: the Hammersmith cohort and the UK Biobank, both comprising individuals of South Asian descent (SA), individuals of Afro‐Caribbean descent (AC), and individuals of European descent (EUR). Regional adipose tissue stores and liver fat were measured by magnetic resonance techniques. Results: The Hammersmith cohort ( n  = 747) had a mean (SD) age of 41.1 (14.5) years (EUR: 374 men, 240 women; SA: 68 men, 22 women; AC: 14 men, 29 women), and the UK Biobank ( n  = 9, 533) had a mean (SD) age of 55.5 (7.5) years (EUR: 4, 483 men, 4, 873 women; SA: 80 men, 43 women, AC: 31 men, 25 women). Following adjustment for age and BMI, no significant differences in visceral adipose tissue or liver fat were observed between SA and EUR individuals in the either cohort. Conclusions: Our data, consistent across two independent UK‐based cohorts, present a limited number of ethnic differences in the distribution of body fat depots associated with metabolic disease. These results suggest that the ethnic variation in susceptibility to features of the metabolic syndrome may not arise from differences in body fat.